TANGGUNG JAWAB PIHAK PENGELOLA KLUB BOLA BASKET SATRIA MUDA PERTAMINA JAKARTA TERHADAP PEMAIN YANG MENGALAMI KECELAKAAN ATAU CEDERA - HARYO AMRIZAL BHAWONO NIM. A1011181089 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTA basketball club is a community or place where players or players can be facilitated by a club to practice and compete in a match as long as the players play for the club. One of the basketball clubs in Indonesia, namely Satria Muda Pertamina, which is located at Jl. Raya Kelapa Nias Kav HF-3 Mahaka Square 3rd Floor, Jakarta. Satria Muda Pertamina was founded in 1993 as one of the newcomer clubs in KOBATAMA (Main Basketball Competition), which is the highest basketball league in Indonesia.The formulation of the problem is as follows: